Expression and pharmacological modulation of visceral pain-induced conditioned place aversion in mice. (March 2016) - Bagdas, Deniz; Muldoon, Pretal P.; AlSharari, Shakir; Carroll, F. Ivy; Negus, S. Stevens; Damaj, M. Imad
Abstract: Pain encompasses both a sensory as well as an affective dimension and these are differentially processed in the brain and periphery. It is therefore important to develop animal models to reflect the non-reflexive assays in pain. In this study, we compared effects of the mu opioid receptor agonist morphine, the nonsteroidal anti-inflammatory drug ketoprofen and the kappa receptor opioid agonist U50, 488H and antagonist JDTic on acetic acid-induced stretching and acetic acid-induced aversion in the condition place aversion (CPA) test in male ICR mice. Intraperitoneal administration of acetic acid (0.32–1%) was equipotent in stimulating stretching and CPA. Ketoprofen, morphine and U50, 488H all inhibited the acid-induced stretching. Ketoprofen and morphine also blocked the acid-induced CPA but U50, 488H failed to do so. The reversal ability of ketoprofen and morphine on acid-induced CPA is unique to pain-stimulated place aversion since these drugs failed to reduce non-noxious LiCl-induced CPA. Overall, this study characterized and validated a preclinical mouse model of pain-related aversive behavior that can be used to assess genetic and biological mechanisms of pain as well as improving the predictive validity of preclinical studies on candidate analgesics. Highlights: Acetic acid (AA) induced stretching and conditioned place aversion (CPA). AA-stretching was blocked by ketoprofen, morphine and U50, 488H but not by JDTic. AA-CPA was blocked by ketoprofen, morphine but not by U50, 488H and JDTic. Neither ketoprofen nor morphine blocked LiCl-induced aversion.